How China anesthesiologists document and communicate difficult airway management - Xiang Luo; Dong Yang; Xiao-Ming Deng; Qian-Yu Wang; Xi-Yu Du (BMC Anesthesiology)
Abstract Background According to the Chinese Society of Anesthesiology, it is recommended that patients with difficult airways be documented and notified, which will provide healthcare professionals with a direct reference when managing airways. However, compliance with this initiative remains unclear. This study was conducted to investigate the current status and need for difficult airway notification at Plastic Surgery Hospital and to explore the factors contributing to noncompliance. Methods Anesthesiologists, surgeons, and patients in Plastic Surgery Hospital were administered separate questionnaires regarding notification of difficult airway management. Participants were surveyed regarding their attitudes and current practices regarding difficult airway notification. In addition, questions were asked regarding the barriers that contribute to noncompliance. Results A total of 632 valid responses were obtained and analyzed, giving a response rate of 99.21%. 399 patients (89.46%) felt it was very important for anesthesiologists to inform them about their difficult airway, and 91.03% felt it was very important for them to receive a letter of their airway assessment. However, twenty-two anesthesiologists (64.7%) reported verbally informing less than 50% of patients about their difficult airway after surgery, and only four anesthesiologists informed all patients they encountered. Most surgeons (91.22%) and anesthesiologists (91.18%) believe that it is vital to inform patients verbally, while 114 surgeons (77.03%) and 31 anesthesiologists (91.18%) believe that it is essential to complete a difficult airway notification alert. Among the factors causing noncompliance, 17 (34.69%) believed that absence of mandatory rules, 9 (18.37%) believed that increased workload, and 8 (16.33%) believed that notification methods were lacking. Conclusions The compliance to difficult airway notification remains low in Plastic Surgery Hospital despite the high incidence of difficult airways. Although anesthesiologists, surgeons, and patients are strongly in favor of it. Among the barriers to compliance were the absence of a well-developed notification system and a means of notification such as an alert form for difficult airways. This may spur the anesthesiology society to publish the notification system.